Impact of age, gender and indigenous status on access to diagnostic coronary angiography for patients presenting with non‐ST segment elevation acute coronary syndromes in Australia. Issue 3 (27th February 2013) - Roe, Y. L.; Zeitz, C. J.; Mittinty, M. N.; McDermott, R. A.; Chew, D. P.
Abstract Using Australian guidelines for management of acute coronary syndromes, we investigated the proportion of high‐risk patients enrolled in the Acute Coronary Syndromes Prospective Audit registry who received a coronary angiogram. A prospective nationwide multicentre registry involving 39 Australian hospitals was used. The study cohort were patients with high‐risk clinical features without ST segment elevation (n = 1948) admitted from emergency departments between 1 November 2005 and 31 July 2007. Eighty nine per cent of patients with ST segment elevation myocardial infarction and only 53% of eligible patients with high‐risk acute coronary syndromes with no ST elevation received a diagnostic angiogram. Increasing age was associated with lower rates of angiography; a high‐risk patient at the age of ≥70 years was 19% less likely to receive an angiogram than one at the age of <70 years (risk ratio (RR) = 0.81 95% confidence interval (CI) 0.76, 0.76). Women were 26% less likely than men to receive an angiogram (RR = 0.74; 95% CI = 0.65, 0.83). The adjusted RR from the multivariate analysis suggests that a patient at the age of ≥70 years was 35% less likely to receive an angiogram than one at the age of <70 years (RR = 0.65, 95% CI = 0.60, 0.73), and that women were 13% less likely than men to receive an angiogram (RR = 0.87, 95% CI = 0.80, 0.96). Indigenous patients were as likely to access angiography as eligible non‐indigenous patients (RR = 1.03, 95% CI 0.85, 1.25). There is underinvestigation of high‐risk patients without ST segment elevation in Australian hospitals, particularly for women and older patients. Indigenous patients are younger and have poorer risk profiles, and represent a group that would benefit from greater investment in prevention strategies.